Interpreting Memory, Forgetfulness and Testimony in Theory of Recollection - Yu, Ni (Bollettino Filosofico, 2016)
The essay is a new attempt to interpret theory of recollection in the context of “the pietas of thinking”. It will explore the different stages of theory of recollection in the Meno with a focus on making enquiry of the conception of episteme. The key conception of episteme is significant in new interpretation of theory of recollection. Its relationship of knowledge and understanding is also decided in the discussion. The essay argues that theory of recollection can be divided into elements of memory, forgetfulness and testimony. Moreover, this division is in accordance with the known elements of mythical story, slave boy demonstration, method of hypothesis in theory of recollection. By making this comparison the value and reason of theory of recollection will be warranted and rediscovered in the new era.